Poor mental health and adverse psychosocial conditions among adolescents in the Nordic countries: contrasting variable- and person-centered analyses - Stattin, Håkan; Eriksson, Charli; Thorsteinsson, Einar Baldvin (Frontiers in Public Health, 2025)
BackgroundThe aim is to compare conclusions about the role of adolescent mental health in adverse psychosocial conditions depending on the analytic approach used (variable-centered vs. person-centered). In the variable-centered analyses, three mental health indicators (psychosomatic complaints, self-rated poor health, and low life satisfaction) were examined in relation to adverse physical, school, interpersonal, and personal conditions. In the person-centered analyses, the three health indicators were used to create mental health profiles using cluster analysis, which were examined in relation to the adverse psychosocial measures.MethodsData were drawn from the HBSC survey of 15-year-olds in 2022. Samples from five Nordic countries were used (N = 7,860). Correlational and cluster analysis were applied.ResultsThe variable-oriented analyses show that all three health indicators were interrelated (ranging between 0.45 and 0.53), form one common factor (with factor loadings ranging from 0.66 to 0.78), and that psychosocial problems do not stand out as having different associations from the other two indicators. Cluster analysis of the three health indicators revealed seven health profiles. These profiles were differentially associated with the outcome measures examined. The health profiles associated with lack of physical activity all included self-rated poor health. The health profiles associated with adverse school, interpersonal, and personal conditions all included high psychosomatic complaints. As a proxy for mental health, psychosomatic complaints have been the primary measure in many previous studies when associated with aversive psychosocial conditions. However, the mental health profile characterized by high levels of psychosomatic complaints exclusively had average levels of these adverse psychosocial measures.ConclusionVariable- and person-centered approaches to the study of adolescent mental health provide complementary insights into the role of the three health indicators in relation to adverse psychosocial conditions. The person-centered approach provides much needed additional information about when a specific health indicator is associated with adverse psychosocial conditions and when it is not. As such, person-centered analyses are needed for future studies in other domains that wish to tell a more complete story as part of their findings.